PENGARUH SUBTITUSI BUNGA KECOMBRANG (Etlingera elatior) TERHADAP KAPASITAS ANTIOKSIDAN COOKIES - Indah Puspita Sari; Mazarina Devi; Ummi Rojahatien (Journal of Food Technology and Agroindustry, 2022)
Kecombrang flower is a plant that has high antioxidant content . The use of kecombrang flowers in food products has not been so much that, it will be useful and add nutritional value when combined with food products. Cookies kecombrang are a snack, including a type of biscuit made from wheat flour, eggs, sugar and fat added with powdered kecombrang flowers. This study is an experimental study using RAL with the aim of knowing the effect of substitution of kecombrang flower powder on cookies with 3 treatments, namely 1%, 2%, and 3% substitution of kecombrang flower powder with 2 repetitions. The resulting data will be analyzed using ANOVA variance and then using the DMRT further test. The results showed that the substitution of 3% sample kecombrang flower powder had the highest antioxidant capacity of 98.77 ppm. Based on the results of the study, the substitution of kecombrang flower powder had an effect on the antioxidant capacity of cookies.